How do Customer Satisfaction and Trust Affect Customer Loyalty in Using Micro Bank Flagship Products? - Rahmawati Rahmawati; Nursinah Amrullah; Andi Naila Quin Azisah Alisyahbana (CV. Sakura Digital Nusantara, 2023)
This study aims to determine the effect of satisfaction and trust on customer loyalty in using the Bank's micro superior products. The research population is Bank customers in Makassar City who use micro superior products. The final sample obtained was 100 respondents. Data analysis used path analysis using Statistical SPSS 25. The results of data analysis show that the satisfaction variable has a significant effect on trust. The satisfaction variable has no positive and significant effect on loyalty. The trust variable has a positive and significant effect on loyalty. Then the analysis of satisfaction on loyalty through trust is known to have a direct effect, while the indirect effect of satisfaction through trust on loyalty, which means that the value of the indirect effect is greater than the value of the direct effect. So it can be concluded that indirectly satisfaction through trust has a significant effect on loyalty. In order to increase consumer loyalty, banks need to continue to improve the quality of their products and services. In addition, banks can provide education to customers to increase customer understanding of the benefits they get from the bank's flagship micro products and how to use them effectively.